The Building Block versus Stumbling Block Debate of Regionalism: From the Perspective of Service Trade Liberalization in Asia - Shintaro Hamanaka (Asian Development Bank (ADB), 2009)
When debating the pros and cons of economic regionalism, haven't we focused enough on trade in goods at the expense of services? This article argues that regionalism is certainly a building block, not a stumbling block to a multilateral trading system, using the services liberalization scheme of Association of Southeast Asian Nations (ASEAN) as a case study. At the same time, it is critical to set out a proper institutional arrangement to ensure that regional services liberalization initiatives reinforce the global services regime. This paper proposes an amendment of the current GATS Article V to define the appropriate relationship between multilateralism and regionalism in the context of services.
hdl:11540/2344
Keywords: F15; O19; 330; GATS; AFAS; ASEAN; services; regionalism; free trade; economic integration